Legal Foundations of the Right to Know - Thomas I. Emerson (Washington University Law Quarterly, 1976)
If we do not make the right to know the main basis for the system of freedom of expression, then what should be the role of that doctrine? There seem to be three general areas in which the right to know may be of special importance. One is the use of the doctrine against direct government interference with the system of freedom of expression. A second is its use in situations where the government seeks to regulate or expand the system by some form of affirmative action. And the third is its use in making information available from government or private sources.
Keywords: Freedom of the press; Privileges